Multivariable Schur-Horn theorems - Massey, Pedro Gustavo (2016)
We prove a variety of results describing the diagonals of tuples of commuting hermitian operators in type II 1  1 factors. These results, motivated by work of Arveson and Kadison, are generalizations of the classical Schur-Horn theorem to the infinite-dimensional, multivariable setting. Our description of these possible diagonals uses a natural generalization of the classical notion of majorization. In the special case when both the given tuple and the desired diagonal have finite joint spectrum, our results are complete. When the tuples do not have finite joint spectrum, we are able to prove strong approximate results. Unlike the single variable case, the multivariable case presents several surprises and we point out obstructions to extending our complete description in the finite spectrum case to the general case. We also discuss the problem of characterizing diagonals of commuting tuples in B ( H ) B(H) and give approximate characterizations in this case as well.